Impact of diabetes mellitus on surgical complications in patients undergoing revision total knee arthroplasty: Insulin dependence makes a difference - Lee, Danny (J Clin Orthop Trauma, 2020)
OBJECTIVES: Assessing the effects of diabetes mellitus (DM), non-insulin-dependent diabetes mellitus (NIDDM), and insulin-dependent diabetes mellitus (IDDM) on revision TKA (rTKA) has become increasingly imperative due to the increased rates of revisions associated with DM. This study sought to identify complications in rTKA that were independently associated with NIDDM/IDDM compared to non-diabetic (Non-DM) patients and whether IDDM was associated with specific postoperative complications compared to NIDDM. METHODS AND MATERIALS: 16,428 rTKA patients were identified from the ACS-NSQIP database from 2005 to 2016 and stratified into three separate cohorts. 12,922 (78.66%) were Non-DM, 2335 (14.21%) had NIDDM, and 1171 (7.13%) had IDDM. Univariate analyses were utilized to assess for differences in demographics, preoperative comorbidities, and postoperative complication rates. Multivariate logistic regression analyses were then employed to control for significant differences in patients characteristics to assess NIDDM and IDDM as independent risk factors for complications in comparison to Non-DM. IDDM was further analyzed as a risk factor in comparison to NIDDM for the purpose of elucidating the impact of insulin dependence on risk for postoperative complications. RESULTS: NIDDM was an independent risk factor for deep incisional surgical site infections (Odds Ratio (OR): 2.477) and urinary tract infections (UTI) (OR 1.862) (p < 0.05). Compared to NIDDM, IDDM was independently associated with greater risk for pneumonia (OR 2.603), septic shock (OR 6.597), blood transfusions (OR 1.326), and an extended length of stay (OR: 1.331) (p < 0.05). IDDM additionally increased the risk for acute renal failure (OR 3.269) and cardiac arrest (OR 3.268) (p < 0.05) when compared to Non-DM. DM patients overall had increased rates of worse outcomes and infectious complications. CONCLUSION: Although differences between diabetes and non-diabetes rTKA patients were seen, differences in complication rates between diabetes patients further divided based on insulin dependence status were also noted. Future work examining whether targeting perioperative glucose levels <200 mg/dL in DM rTKA patients decreases infectious complications is warranted. Future work analyzing the role of tranexamic acid administration and 24-h postoperative antibiotics in rTKA IDDM patients may be warranted given the elevated risk of pneumonia, septic shock, and blood transfusions.